Patterns of opioid dose escalation in patients with chronic kidney disease initiated on opioids for the treatment of non-cancer pain - Che Suraya Zin; Stefania Lando; Ailema González-Ortiz; Viyaasan Mahalingasivam; Shayan Mostafaei; Wan Rohaidah Ahmad; Mazlila Meor Ahmad Shah; Björn Wettermark; Juan Jesus Carrero (PLoS ONE, 2026)
Background Pain management in chronic kidney disease (CKD) is challenging due to altered drug metabolism, impaired excretion, and higher opioid toxicity risk. Despite this, opioids are commonly prescribed, yet real-world data on dose escalation in CKD remain limited. Objective To investigate patterns and timing of opioid dose escalation to ≥50 and ≥90 MME/day among new opioid users across kidney function levels. Methods This population-based cohort study used data from the Stockholm Creatinine Measurements (SCREAM) project linking diagnoses, prescriptions, and laboratory records. Adult new opioid users (no prior opioid in 12 months) from 2012–2021 were categorized by baseline eGFR (≥60, 30–59, < 30 mL/min/1.73m²). Opioids were identified using ATC codes, and daily doses (MME/day) were calculated based on strength, quantity, and equianalgesic ratios. Fine–Gray competing-risks regression assessed time to dose escalation (≥50 and ≥90 MME/day), accounting for death as a competing event. Results Of 81,987 adult new opioid users, 5,987 (7.3%) escalated to ≥50 MME/day comprising 7.4%, 6.8%, and 8.1% of patients with eGFR ≥ 60, 30–59, and <30 mL/min/1.73m², respectively. For ≥90 MME/day, 2,067 (2.5%) escalated, 2.5%, 2.3%, and 2.9% across the same eGFR categories. Competing risks regression showed significantly lower risks of escalation among patients with reduced eGFR levels. For ≥50 MME/day, the sub distribution hazard ratios (SHRs) were 0.67 (95% CI: 0.56–0.81, p < 0.001) for eGFR 30–59 and 0.64 (95% CI: 0.42–0.99, p = 0.043) for those with eGFR < 30.For ≥90 MME/day, SHRs were 0.57 (95% CI: 0.43–0.75 , p < 0.001 )and 0.31(95% CI: 0.15–0.65, p = 0.002 ), respectively. Most escalation occurred within six months, with minimal increase thereafter. Conclusion Opioid dose escalation occurred across all eGFR levels, underscoring the need for cautious, individualized prescribing and close monitoring, especially in patients with reduced kidney function.